Effectiveness of empiric cardioprotective therapy in patients receiving cardiotoxic chemotherapies: systematic review & bayesian network meta-analysis. (11th May 2022) - Abdelfattah, OM; Sayed, AS; Munir, M; Shazly, O; Awad, AK; Ghaith, HS; Gerew, M; Guha, A; Barac, A; Fradley, MG; Abela, GS; Addison, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardioprotective therapies represent an important avenue to reduce these limiting toxicities, including serious heart failure (HF) events. However, due to conflicting isolated reports, the true efficacy and optimal cardioprotective therapy at the time of anticancer treatment initiation is unclear. Therefore, we undertook a network meta-analysis to elucidate the most effective therapies at cardiotoxic HF prevention. Purpose: To determine the efficacy, and optimal cardioprotective strategy in patients receiving cardiotoxic chemotherapies. Methods: Leveraging the MEDLINE/Pubmed, CENTRAL, and clinicaltrials.gov databases, we identified all randomized controlled trials (RCTs) investigating cardioprotective therapies from inception to November 2021. Eligible cardioprotective classes included ACEIs, ARBs, Beta-blockers, dexrazoxane (DEX), statins, and mineralocorticoid receptor antagonists (MRA). The primary endpoint was the prevention of new-onset HF. The secondary outcomes were the mean difference in left ventricular ejection fraction (LVEF) change, the incidence of hypotension, and all-cause mortality. Network meta-analyses were used to assess the cardioprotective effects of each therapy to deduce the most effective therapies. Both analyses were undertaken using a Bayesian random-effects model to estimate risk ratios (RR) and 95% credible intervals (95% CrI). Results: Overall, from 726 articles, 39 studies evaluating 5, 931 participants (38.0±19.1 years, 72.0% females) were identified. Over a median follow-up of 6 months, use of any cardioprotective strategy was associated with a significant reduction in new-onset HF (RR:0.32; 95% CrI:0.19-0.55), improved LVEF (mean difference: 3.92%; 95% CrI:2.81-5.07), and increased hypotension (RR:3.27; 95% CrI:1.38-9.87); there was no difference in mortality (RR:1.03; 95% CrI:0.84-1.22). Based on the median risk of incident HF in the control groups being 3.28%, the number need to treat (NNT) for "any" cardioprotective therapy to prevent one incident HF event was 45 patients. For dexrazoxane and neurohormonal agents, the median NNT was 36 and 53 patients, respectively. In this network analysis, dexrazoxane was most effective at HF prevention [Surface Under the Cumulative Ranking curve (SUCRA): 81.47%] and MRA most effective at preserving LVEF (SUCRA: 99.22%). ARBs most greatly increased hypotension (RR:7.20; 95% CrI:2.46-26.94). Conclusion: Cardiotoxicity remains a challenge for cancer patients requiring life-saving cancer therapies. The initiation of a cardioprotective strategy reduces incident HF. Additional head-to-head trials are needed to confirm the optimal preventative strategy.